Selected demographic variables and community policing participation among citizens in Nigeria: a pilot study - Abubakar, Dalhatu Saidu; Othman, Zaheruddin; Mustaffa, Jamaludin (2017)
In consideration of increase in crime rate and societal ills, Nigeria must improve upon its security architecture and policies to ensure security of live and property in the country. Effective community policing through increases citizens’ participation is of paramount importance.This paper is a pilot research study of the upcoming main study which intends to investigate community policing participation intention among Nigerian citizens. Thus, the paper examines small sample of data on the impact of ethnicity, religion, trust in the police, and attitudes toward the police on intention to participate in community policing program in Nigeria.The study utilizes survey questionnaire to obtain data. The survey questionnaire was at the beginning subjected to content validation.The reviewed version of the survey was distributed to the pilot sample.The returned survey was scrutinized for reliability using SPSS version 16.0. The results indicate that the instrument attained the thresh hold, therefore valid and reliable.Additionally, the data shows evidence of practical consistency.